Household Wood Fuel Usage and Lung Cancer Predictor Symptoms in Primary Care: A Retrospective Cross-Sectional Study for Lung Cancer Early Detection - Adriel Wiemputra Wangsa; Wahyu Pamungkasih (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Biomass fuel combustion is a major contributor to household air pollution, posing risks to various health concerns, including lung cancer (LC). In Yogyakarta, 13.68% of households still depend on firewood as their primary source of cooking fuel. This retrospective cross-sectional study involved 302 patients attending the outpatient department at Pundong District Health Centre between July and August 2023. The primary outcomes were the number of reported LC predictor symptoms and LC suspicion referral status, based on the NG12 referral criteria. Wood fuel usage (WFU), respiratory disease history, and smoking history were the independent factors. Significant symptoms associated with high-risk WFU were cough (OR = 3.16, p < 0.001), dyspnoea (OR = 3.66, p = 0.001), fatigue (OR = 2.26, p = 0.016), and weight loss (OR = 4.46, p = 0.043). WFU and respiratory disease history were significantly associated with the number of LC predictor symptoms (p < 0.001). WFU, respiratory disease history, and smoking history demonstrated a significant relationship with LC suspicion referral status (p < 0.001). This study highlights the association between WFU and LC predictor symptoms, as well as the need for LC suspicion referral in limited resources settings. Further research is needed to validate the LC predictor symptoms with radiologic findings and final diagnosis.